A CT Angiographic Study on the Variations of the Hepatic Arteries in the Living Liver Donors of the South Indian Population.: Life Sciences-Anatomy - Ashok, P; Raghunath, Gunapriya; Anantha Kumari, V; Shiny Vinila, B. H (International Journal of Life Science and Pharma Research, 2022)
Living liver donor transplantation is the last option for the end stage liver diseases. The variations in the hepatic artery of the liver donor may lead to poor outcome, or may end with major post-operative complications such as hepatic artery thrombosis. To prevent the post-operative complications and to increase the success rate of the liver transplant surgeries, CT evaluation of the hepatic arteries is essential. Thus, the present study was aimed to study the variations of the hepatic arteries in the living liver donors. A total of 200 CT angiograms were collected from the department of Radiology from August 2018 to December 2021, and the evaluation was carried out in the Department of Anatomy, Deccan College of Medical Sciences, Hyderabad. All the CT angiograms were studied for the variations of hepatic arterial system, and the observed variations were noted and the incidence was calculated. The normal anatomy was observed in 62.5% liver donors and 37.55% of liver donors showed variations in hepatic arterial pattern. The incidence of the replaced left hepatic retry, replaced right artery, replaced left along with replaced right hepatic artery was observed as 11.5%, 9.5% and 3% respectively. The incidence of left and right accessory hepatic arteries was 7% and 4% respectively and the replaced right hepatic artery with accessory left hepatic artery was observed in 1.5% cases. The variations observed in the hepatic arterial pattern observed in this study could be helpful to the surgeons, while planning and selecting the suitable liver donors and also may minimise the risk and increase the success rate.